(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Hepatitis B virus (HBV) is an enveloped DNA virus which causes hepatitis B infection in the world. It is mainly passed on by coming in contact with infectious body fluids especially blood and mucosal secretions. Hepatitis B is a systemic infection; its main location of viral replication is the liver; the disease is characterized by fever, jaundice, and the gastrointestinal tract. The major aim of the current research is to evaluate prevalence and distribution of HBV among adolescent population. Ninety-seven samples were collected among adolescent patients in Azadi Teaching Hospital between the months of June and October 2025 to identify the prevalence of HBV. Serological analysis of blood was done to identify hepatitis B surface antigen (HBsAg) by enzyme linked immunosorbent assay (ELISA). Out of the 97 sample in study, 26 were positive in HBsAg, which was a prevalence of 26.8. Most of the carriers were male (64⠻¹) and a significant percentage 83.5 was metropolitan. The age of the participants was between 11-19 years. The statistics show that the risk of someone to contract hepatitis B is statistically significant among male population than it is among women, which could be explained by cultural-oriented activities that expose more men to outdoor activities and consequently to potentially contaminated objects or infected people. Most of the subjects of this study were urban residents, a trend that accounts to similar studies that have been done in other places. Despite the fact that blood transfusion is one of the unavoidable aspects of modern healthcare, blood transfusion is not always free of any infectious agents which can be transmitted. The use of non-sterile injection needles and exposure to risky tattooing or piercing activities also increase the prevalence rates of hepatitis B among the adolescents. Therefore, the effectiveness of preventive strategies can be undermined when the target population is not properly informed on the risks of acquiring hepatitis B virus (HBV) that are associated with it. In order to curb the prevalence of HBV, it is of urgent importance that all people should be properly vaccinated and be well aware of the potential dangers of the virus.